PH-Responsive, two-in-one doxorubicin and Bcl-2 siRNA-loaded micelleplexes for triple-negative breast cancer therapy. Issue 39 (6th September 2022) - Lu, Hung-Hsun; Liu, Hsueh Wen; Dinh, Trinh Kieu; Huang, Cheng-Hung; Huang, Hsi-Chien; Tseng, Ya-Ching; Ku, Man-Hsuan; Wang, Fu-Sheng; Chen, Yunching; Peng, Chi-How
Abstract : Triblock copolymer, PEG- b -PDMAEMA- b -PDPA, simultaneously encapsulated doxorubicin and Bcl-2 siRNA for delivery to cancer cells, thus achieving combination chemotherapy and gene therapy. Abstract : The combination of chemotherapy and gene therapy is a versatile strategy for treating multi-drug-resistant cancer. Accordingly, we developed a pH-responsive triblock copolymeric carrier for delivering chemotherapeutic and genetic drugs simultaneously. We synthesized a series of block and random copolymers with the same monomer composition, namely poly(ethylene glycol)- b -poly(2-(dimethylamino)ethyl methacrylate)- b -poly(2-(diisopropylamino)ethyl methacrylate) (PEG- b -PDMAEMA- b -PDPA) and poly(ethylene glycol)- b -poly[(2-(dimethylamino)ethyl methacrylate)- r -(2-(diisopropylamino)ethyl methacrylate)] (PEG- b -(PDMAEMA- r -PDPA)), by using atom transfer radical polymerization (ATRP) and then used them to encapsulate and release doxorubicin (Dox) and Bcl-2 siRNA. Compared with the random copolymers, the block copolymers exhibited a higher Dox-loading efficiency and Dox-loading capacity and higher Bcl-2 siRNA condensation efficiency. The siRNA condensation efficiency could be increased by increasing the length of the PDMAEMA segment in either the block copolymers or random copolymers. PEG- b -PDMAEMA- b -PDPA encapsulated Dox and Bcl-2 siRNA to form Dox/Bcl-2 siRNA-loaded micelleplexes with 87% and 90% loading efficiency, respectively. Changing the pH value from 7.4 to 5.0 engendered a burst release of Dox and Bcl-2 siRNA from the Dox/Bcl-2 siRNA-loaded micelleplexes, thus enhancing the cumulative release efficiency of Dox from 24% to 69% and that of Bcl-2 siRNA from 15% to 59% within 24 h. Our in vitro study revealed that the Dox/Bcl-2 siRNA-loaded micelleplexes downregulated Bcl-2 mRNA expression (51% expression) and further inhibited antiapoptotic mechanisms to sensitize drug-resistant triple-negative breast cancer (TNBC) cells to Dox (36% cell viability); this thus demonstrates the benefits of combining chemotherapy and gene therapy.